On existence of periodic solutions of the Rayleigh equation of retarded type - Genqiang Wang; Jurang Yan (International Journal of Mathematics and Mathematical Sciences)
In this paper, we give two sufficient conditions on the existence of periodic solutions of the non-autonomous Rayleigh equation of retarded type by using the coincidence degree theory.